RPGRorf15 nanopore long-read sequencing improves retinitis pigmentosa molecular diagnosis for men and women - Manon Fabard; Aurore Devos; Anaïs F. Poncet; Jean-Pascal Meneboo; Martin Figeac; Céline Villenet; Isabelle Drumare; Sabine Defoort-Dhellemmes; Isabelle Meunier; Xavier Zanlonghi; Olivier Grunewald; Vincent Huin; et al. (Human Genetics, 2026)
RPGR (Retinitis Pigmentosa GTPase Regulator ) is the main gene involved in X-linked retinitis pigmentosa (RP) and up to 28% of sporadic RP. Pathogenic variants are mostly located in its retina-specific transcript, RPGRorf15 , especially in the terminal exon named open reading frame 15 (ORF15) , which is a highly repeated region. Because of this complex sequence, first- and second-generation short-read sequencing are difficult, both for male patients and for affected and relative females, resulting in numerous unresolved cases. Long-read sequencing appears to be the most appropriate to counter this problem. Using Oxford Nanopore Technology sequencing, we analysed 194 patients with retinal dystrophy (RD) (142 men and 52 women) suspected to be either X-linked ( n = 42) or autosomal ( n = 152), and for whom first-line sequencing of 230 retinal dystrophy genes, including RP2 and RPGRex1-19 , was negative. Pathogenic ORF15 variants were found in 27 patients (13.9%), 21 men and 6 women. Of the 42 XLRD patients, 15 were carriers (35.7%), nine men and six women, most of them had rod-cone dystrophy. Of the 152 patients with isolated RD, only 12 carried ORF15 variants (7.9%),all male patients, most of them had cone-rod dystrophy (41.7%). We demonstrate the efficacy of this technology to diagnose male cases with a family history of X-linked RD, as well as sporadic cases clinically not suggestive of ORF15 . We also show how easy it is to analyse female carriers or affected women. We expect that more heterozygous women with severe disease and no family history will be identified by this technique in the future.

Supercritical water gasification of polyolefins and polystyrene-based polymers - Tiphaine Benoist; Alban Chappaz; Léa Vilcocq; Vincent Monteil; Pascal Fongarland; Hary Demey (Chemical Engineering Journal, 2026)

Heterospecific social behavior in primates: insights into the evolutionary roots of pet-keeping - Cyril C. Grueter; Fany Roncin; K. Anne-Isola Nekaris; Jill Pruetz; Richard McFarland; Sabit Hasan; Malgorzata Arlet; Timothy M. Eppley; Susan M. Cheyne; Vincent Nijman; Eckhard W. Heymann; Pascal R. Marty; et al. (Primates, 2026)
Primate interspecific interactions with both other primates and non-primate species range from predator–prey dynamics to affiliative behaviors such as grooming, play, and carrying. While many primates participate in interspecific associations or commensal relationships, to our knowledge interspecific social interactions have never been systematically synthesized. Here, we present the first comprehensive review of such interactions, compiling 427 cases from the literature, media sources, and a global survey of primatologists. These involved 88 primate species and 127 non-primate species (including mammals, birds, reptiles, amphibians, malacostracans, and insects) across wild (n = 311) and captive (n = 111) contexts. The most frequent interactions occurred within or between primate families (e.g., Cercopithecidae–Cercopithecidae, Cebidae–Atelidae), though affiliative behaviors were also directed toward distantly related taxa such as dogs and birds. Play (n = 139) and grooming (n = 136) were most common. Juveniles and infants predominantly engaged in play, while adult females were more likely to groom. Adult males were less affiliative overall. Contrary to expectations, affiliative behaviors were not more often directed toward immature than adult heterospecifics. Primates were the initiators in most interactions. These findings offer new insights into the diversity and contexts of heterospecific sociality in primates and suggest that some behavioral tendencies relevant to later forms of human–animal companionship – such as caregiving, tolerance, and exploratory play – may be more widespread among primates than previously recognized.

Short-term response of nematode communities, earthworms and straw decomposition to organic residual products application in mesocosm experiments with three different soils - Kevin Hoeffner; Camille Chauvin; Cécile Villenave; Florian Vautrin; Grégory Vrignaud; Pierre Barré; Daniel Cluzeau; Samuel Dequiedt; Vincent Jean-Baptiste; Pierre Alain Maron; Pascal Piveteau; Lionel Ranjard; et al. (Applied Soil Ecology, 2026)

Fatty acid profiles of muscle and liver reveal ontogenetic shifts in diet and reproductive investment in an undulate ray from the Bay of Biscay (northeast Atlantic) - Pablo Brosset; Tino Jamme; Bastien Sadoul; Manuel Vlach; Pascal Lorance; Vincent Rioux; Salomé Fabri‐Ruiz (Journal of Fish Biology, 2026)
Elasmobranchs, with their slow growth, long lifespans and low reproductive output, are particularly sensitive to fluctuations in nutritional status and energy availability throughout ontogeny. Fatty acids serve as valuable biomarkers for studying trophic ecology, ontogenetic dietary shifts and energy allocation during key life periods such as growth and reproduction. This study examined fatty acid profiles in Raja undulata by analysing muscle and liver tissues to investigate ontogenetic dietary shifts, assess niche breadth and overlap between juveniles and adults, and explore how reproductive development influences fatty acid allocation after sexual maturity. The muscle fatty acid profiles of R. undulata varied across life stages, with adults showing a reduced trophic niche and a diet composed of higher‐trophic‐level prey compared to juveniles. This pattern suggested a dietary shift from a diverse, invertebrate‐based diet in juveniles to more specialized predation on fish and larger crustaceans in adults. The liver fatty acid profiles varied across reproductive stages, with an increasing proportion of omega‐3 (C22:6n‐3, docosahexaenoic acid [DHA]; 22:5n‐3, docosapentaenoic acid) and omega‐6 polyunsaturated (C20:4n‐6, arachidonic acid [ARA]) fatty acids, alongside a marked decline in eicosapentaenoic acid (C20:5n‐3), likely reflecting its direct allocation to the ovaries. Additionally, the elevated monounsaturated fatty acids levels in adults and their decline during gametogenesis highlighted their key role as energy sources for oocyte development, supporting previous findings on reproductive energy mobilization in elasmobranchs. While DHA and ARA proportions increased, their stable absolute values suggested a different allocation pattern compared to viviparous species, potentially due to R. undulata 's oviparous strategy. Our findings, in line with previous studies, showed that analysing different tissues is key to understanding how diet and energy use are linked in elasmobranchs.

Impact of acute sleep restriction on resting ventilation and cytokine levels in normobaric hypoxia, and their association - Louis David; Julianne Touron; Marie-Claire Erkel; Catherine Drogou; Anaïs Pontiggia; Vincent Beauchamps; Carine Malle; Olivier Nespoulous; Ulysse Comte; Alexandra Malgoyre; Fabien Sauvet; Beth A. Beidleman; et al. (European Journal of Applied Physiology, 2026)

Deglaciation of Anticosti Island (eastern Canada) and its implications on climate-driven dynamics of the Laurentide Ice Sheet margin - Pierre-Olivier Couette; Pascal Bernatchez; Vincent Rinterknecht; Bernard Hétu; Jérôme Dubé; Patrick Lajeunesse (Quaternary Science Reviews, 2026)

Decline in cardiorespiratory fitness and its association with vascular aging and subclinical atherosclerosis in healthy older adults: a 3-year longitudinal study - Vincent Groesser; Christopher Weyh; Torsten Frech; Natascha Sommer; Klaus Eder; Astrid Most; Samuel Sossalla; Karsten Krüger; Pascal Bauer (GeroScience, 2026)
Aging is associated with progressive deterioration of vascular function and cardiovascular risk. Cardiorespiratory fitness (CRF) is closely associated with cardiovascular health, yet longitudinal data in healthy older adults remain limited. This study examined 3-year changes in vascular and echocardiographic parameters in older adults and their associations with CRF and muscle strength. Forty-nine participants (mean age 63.8 ± 3.8 years) underwent vascular assessments (brachial/central blood pressure (BP), pulse wave velocity (PWV), augmentation index), echocardiography, CRF testing via spiroergometry to determine VO 2 peak, muscle strength testing, and carotid sonography at baseline and after 3 years. Participants were grouped by carotid plaque status: no atherosclerosis, existing atherosclerosis, or newly developed atherosclerosis. Over 3 years, CRF and muscle strength (grip strength, leg flexion) declined significantly (all p < 0.005), while systolic BP ( p = 0.042), brachial-ankle PWV ( p = 0.006), and echocardiographic parameters including aortic root diameter and ventricular dimensions increased (all p < 0.001). Participants with newly developed atherosclerosis showed the greatest CRF decline ( p = 0.012). Changes in CRF were inversely associated with changes in systolic, diastolic, and central BP (all p < 0.01). Declines in leg flexion strength were also linked to larger BP increases. Participants maintaining > 90% of baseline VO 2 peak had significantly smaller BP increases. These results indicate that vascular aging progresses measurably within a few years in clinically healthy older adults and is associated with declines in CRF and muscle strength. Preservation of CRF is linked to more favorable vascular aging profiles and a lower prevalence of newly developed atherosclerosis. Graphical Abstract

Patient-derived complex organoids are a critical tool to understand and explore pediatric malignant brain tumors - Marlène Deschuyter; Sophie Martin; Chinar Salmanli; Clémence Hubsch; Audrey Vincent; Samuel Meignan; Alessandro Furlan; Erika Cosset; Hélène Burckel; Georges Noel; Michel Salzet; Marie Duhamel; et al. (Cancer and Metastasis Reviews, 2026)

High-frequency fluorescence monitoring in karst aquifers: A multivariate approach for early detection of anthropogenic contamination of water resources - Lucile Justy; Vincent Bailly-Comte; Pascal Brunet; Christelle Batiot-Guilhe (Science of The Total Environment, 2026)

Solid and liquid fractions of digestate: manure or slurry just like any others? - Florian Vautrin; Mario Cannavacciuolo; Camille Chauvin; Pascal Piveteau; Pierre Barré; Cécile Villenave; Daniel Cluzeau; Kevin Hoeffner; Pierre Mulliez; Vincent Jean-Baptiste; Gregory Vrignaud; Aurélien Cottin; et al. (Applied Soil Ecology, 2026)

Clinical spectrum of ICU-acquired invasive pulmonary aspergillosis according to SARS-CoV2 infection: a multicenter prospective cohort study - Florian Reizine; Mattéo Mauget; Nicolas Massart; Yannick Fedun; Anaïs Machut; Charles-Hervé Vacheron; Anne Savey; Arnaud Friggeri; Alain Lepape; Melissa Abbes; Abdelkrim Abdelmalek; Francoise Adema; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Congo Basin Carbon Cycle Responses to Global Change - Sarah Worden; Rong Fu; A. Anthony Bloom; Marijn Bauters; Hans Verbeeck; Temilola Fatoyinbo; Wannes Hubau; Lydie‐Stella Koutika; Steve Kwatcho Kengdo; Sybryn L. Maes; Vincent Medjibe; Nicholas J. Russo; et al. (Global Change Biology, 2026)
The Congo Basin and its contiguous forests harbor globally significant carbon stocks, estimated at 65 gigatons of C (GtC) above and belowground. Despite rising temperatures and intensifying droughts, they have remained a carbon sink, albeit weak: 0.26–0.50 GtC yr. −1 carbon uptake since 1980. However, these forests' carbon stocks and fluxes, including gross primary productivity, respiration, net primary productivity, and riverine carbon transport, remain poorly quantified. This limits understanding of the region's role in the global carbon cycle, its vulnerability to environmental change, and its potential as a long‐term carbon sink. We review and quantify Congo Basin and contiguous forest carbon stocks and fluxes and synthesize the current knowledge on how key global change drivers shape the region's carbon cycle. We find limited responses to long‐term precipitation variability, but declining stocks and fluxes in response to long‐term and increasing temperature and drought frequency. Land cover and land use changes, largely driven by small‐scale agriculture, logging, and agro‐industrial expansion, reduce carbon stocks, ecosystem structure and functioning, and animal‐mediated ecosystem services. In contrast, large‐scale savanna biomass burning delivers phosphorus and nitrogen to Congo Basin forests via cross‐equatorial winds, providing additional nutrients and supporting carbon sequestration. In situ studies suggest that CO 2 fertilization has increased intrinsic water‐use efficiency, although its effects may be modulated by climate change, and its impacts on biomass accumulation remain uncertain. Legacy effects from historical land use and climate change likely shaped present‐day vegetation structure, yet their relative influence is unclear. High‐resolution carbon monitoring, improved remote sensing, and strengthened in situ measurement networks are needed to quantify the impacts of these key drivers and their interactions on the Central African carbon cycle. This is needed to inform conservation strategies and advance understanding of the region's future as a carbon sink under global change pressures.

Persistent organic pollutants in food systems: A comparative study across four contrasting socio-ecosystems: Portugal, Senegal, French Guiana, and Guadeloupe - Nathalie El Deghel; Michael Rapinski; Priscilla Duboz; Richard Raymond; Damien Davy; Nuno Durães; André-Marie Dendievel; Eduardo Ferreira da Silva; Pascal Jean Lopez; Vincent Vaccher; Anaïs Vénisseau; Julie Anne Nazare; et al. (Food Chemistry, 2025)

Effect of double-diffusion processes in the deep ocean on the distribution and dynamics of particulate and dissolved matter: a case study in the Tyrrhenian Sea - Xavier Durrieu de Madron; Paul Blin; Mireille Pujo-Pay; Vincent Taillandier; Pascal Conan (Ocean Science, 2025)
This study examines conductivity–temperature–depth (CTD), acoustic Doppler current profiler (ADCP) and optical data collected during the PERLE-3 cruise in March 2020 between the surface and 2000 m depth over an east–west section of the Tyrrhenian Sea in the Mediterranean. The focus is on the impact of double-diffusion processes, in particular salt fingering, on the distribution and dynamics of particulate and dissolved matter. Staircases form at the interface between the warm, saline Eastern Intermediate Water (EIW) and the colder, less saline Tyrrhenian Deep Water (TDW) in the centre of the basin in a region of weak hydrodynamic activity. The results show that thermohaline staircases formed by salt fingering significantly influence particle sedimentation and biogeochemical cycling in deep ocean environments by altering vertical flux patterns. These density steps create distinct vertical layers that act as physical barriers, slowing the descent of particles and facilitating their retention and aggregation. The retention of fine particles at density gradients promotes the formation of larger aggregates, thereby affecting the particle size distribution. The staircases also affect dissolved matter by creating pronounced concentration gradients of oxygen and nutrients, which may influence microbial activity and nutrient fluxes.

Agri-STAMP: A spatial model representing the use and fate of pesticides over the long term - Annelise Tran; Victor Dufleit; Vincent Bonnal; Pascal Degenne; Jeremy Lavarenne; Lucie Lecat; Philippe Cattan (Science of The Total Environment, 2025)

Iron fortification modifies the microbial community structure and metabolome of a model surface-ripened cheese - Mahtab Shoukat; Vincent Hervé; Anne-Sophie Sarthou; Anne-Claire Peron; Alice Danel; Dominique Swennen; Pascal Bonnarme; Eric Dugat-Bony (International Journal of Food Microbiology, 2025)

An approach to Molten Salt Reactor operation and control and its application to the ARAMIS actinide burner - Martin Mascaron; Johann Martinet; Vincent Pascal; Elsa Merle; Frédéric Bertrand (Annals of Nuclear Energy, 2025)

Spatial and seasonal abundance and characteristics of microplastics along the Red River to the Gulf of Tonkin, Vietnam - Thi Thao Nguyen; Van Hoi Bui; Stéphanie Lebarillier; Toan Khanh Vu; Pascal Wong-Wah-Chung; Vincent Fauvelle; Laure Malleret (Science of The Total Environment, 2024)

MORPHEE a multiphysics tool for control rod withdrawal modeling in SFR - Marlène Jeannin; Laurent Buiron; Vincent Pascal (Annals of Nuclear Energy, 2024)

Venom peptides as promising tools for lung cancer diagnosis - Romain Baudat; Evelyne Benoit; Pascal Kessler; Benoit Jego; Mathilde Keck; Vincent Thomas De Montpreville; Charles Truillet; Denis Servent (Toxicon, 2024)

Mesoscale variability of phosphorus stocks, hydrological and biological processes in the mixed layer in the Eastern Mediterranean Sea in autumn and during an unusually dense winter phytoplankton bloom - France Van Wambeke; Vincent Taillandier; Xavier Durrieu de Madron; Pascal Conan; Mireille Pujo-Pay; Stella Psarra; Sophie Rabouille; Chloé Baumas; Elvira Pulido-Villena (Deep Sea Research Part I: Oceanographic Research Papers, 2024)

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

Long-Term Follow-Up of Cerebral Aneurysms Completely Occluded at 6 Months After Intervention with the Woven EndoBridge (WEB) Device: a Retrospective Multicenter Observational Study - Kareem El Naamani; Panagiotis Mastorakos; Nimer Adeeb; Mathews Lan; James Castiglione; Omaditya Khanna; Jose Danilo Bengzon Diestro; Rachel M. McLellan; Mahmoud Dibas; Justin E. Vranic; Assala Aslan; Hugo H. Cuellar-Saenz; et al. (Translational Stroke Research, 2024)

Farming activity and risk of treated thyroid disorders: Insights from the TRACTOR project, a nationwide cohort study - Pascal Petit; Sylvain Chamot; Abdallah Al-Salameh; Christophe Cancé; Rachel Desailloud; Vincent Bonneterre (Environmental Research, 2024)

Sialic acids cleavage induced by elastin-derived peptides impairs the interaction between insulin and its receptor in adipocytes 3T3-L1 - Alexandre Guillot; Kevin Toussaint; Lucrece Ebersold; Hassan ElBtaouri; Emilie Thiebault; Tarik Issad; Franck Peiretti; Pascal Maurice; Hervé Sartelet; Amar Bennasroune; Laurent Martiny; Manuel Dauchez; et al. (Journal of Physiology and Biochemistry, 2024)

Association of cardiorespiratory fitness level with vascular function and subclinical atherosclerosis in the elderly - Vincent Größer; Christopher Weyh; Tim Böttrich; Torsten Frech; Svenja Nolte; Natascha Sommer; Magdalena Huber; Klaus Eder; Oliver Dörr; Sophie Hoelscher; Rebecca Weber; Ebru Akdogan; et al. (European Journal of Applied Physiology, 2024)
Purpose Physical exercise is crucial for healthy aging and plays a decisive role in the prevention of atherosclerotic cardiovascular disease (ASCVD). A higher level of cardiorespiratory fitness (CRF) in the elderly is associated with lower cardiovascular and all-cause mortality. This study investigated the association of CRF level with vascular function and cardiovascular risk factors in the elderly. Methods We examined 79 apparently healthy and physically active subjects aged > 55 years (64 ± 4 years). Cardiovascular functional parameters assessed included brachial and central blood pressure (BP), pulse wave velocity (PWV), augmentation index (Aix), and ankle-brachial index. Sonography of the common carotid artery was performed. CRF level was determined by a cardiopulmonary exercise test, and everyday activity was quantified with an accelerometer. Results All participants had a higher CRF level than the reported age-specific normative values. Twenty-nine subjects had subclinical atherosclerosis of the common carotid artery. Compared with participants without atherosclerosis, they were older ( p = 0.007), displayed higher brachial systolic BP ( p = 0.006), and higher central systolic BP ( p = 0.014). Lower brachial ( p = 0.036) and central ( p = 0.003) systolic BP, lower PWV ( p = 0.004), lower Aix ( p < 0.001), lower body fat percentage (< 0.001), and lower LDL cholesterol ( p = 0.005) were associated with a higher CRF level. Conclusions In this cohort of healthy and physically active individuals, subjects with subclinical atherosclerosis displayed higher systolic brachial and central BP. A higher CRF level was associated with enhanced vascular function, consistent with an influence of CRF on both BP and vascular function in the elderly.

Association of central blood pressure with an exaggerated blood pressure response to exercise among elite athletes - Astrid Most; Lutz Kraushaar; Oliver Dörr; Stanislav Keranov; Sophie Hoelscher; Rebecca Weber; Ebru Akdogan; Vincent Groesser; Faeq Husain-Syed; Holger Nef; Christian W. Hamm; Pascal Bauer (European Journal of Applied Physiology, 2024)
Purpose The systolic blood pressure/workload (SBP/MET) slope was recently reported to be a reliable parameter to identify an exaggerated blood pressure response (eBPR) in the normal population and in athletes. However, it is unclear whether an eBPR correlates with central blood pressure (CBP) and vascular function in elite athletes. Methods We examined 618 healthy male elite athletes (age 25.8 ± 5.1 years) of mixed sports with a standardized maximum exercise test. CBP and vascular function were measured non-invasively with a validated oscillometric device. The SBP/MET slope was calculated and the threshold for an eBPR was set at > 6.2 mmHg/MET. Two groups were defined according to ≤ 6.2 and > 6.2 mmHg/MET, and associations of CBP and vascular function with the SBP/MET slope were compared for each group. Results Athletes with an eBPR ( n = 180, 29%) displayed a significantly higher systolic CBP (102.9 ± 7.5 vs. 100 ± 7.7 mmHg, p = 0.001) but a lower absolute (295 ± 58 vs. 384 ± 68 W, p < 0.001) and relative workload (3.14 ± 0.54 vs. 4.27 ± 1.1 W/kg, p < 0.001) compared with athletes with a normal SBP/MET slope ( n = 438, 71%). Systolic CBP was positively associated with the SBP/MET slope ( r = 0.243, p < 0.001). In multiple logistic regression analyses, systolic CBP (odds ratio [OR] 1.099, 95% confidence interval [CI] 1.045–1.155, p < 0.001) and left atrial volume index (LAVI) (OR 1.282, CI 1.095–1.501, p = 0.002) were independent predictors of an eBPR. Conclusion Systolic CBP and LAVI were independent predictors of an eBPR. An eBPR was further associated with a lower performance level, highlighting the influence of vascular function on the BPR and performance of male elite athletes.

Photodegradation of disposable polypropylene face masks: Physicochemical properties of debris and implications for the toxicity of mask-carried river biofilms - Isabelle Bihannic; Renaud Gley; Lucas Gallo; Apolline Badura; Angelina Razafitianamaharavo; Maximilien Beuret; David Billet; Clément Bojic; Céline Caillet; Philippine Morlot; Marie Zaffino; Fatina Jouni; et al. (Journal of Hazardous Materials, 2024)

Does prenatal exposure to multiple airborne and tap-water pollutants increase neonatal thyroid-stimulating hormone concentrations? Data from the Picardy region, France - Sylvain Chamot; Abdallah Al-Salameh; Pascal Petit; Vincent Bonneterre; Christophe Cancé; Guillaume Decocq; Agnès Boullier; Karine Braun; Rachel Desailloud (Science of The Total Environment, 2023)

Correction to: The Woven EndoBridge (WEB) Device for the Treatment of Intracranial Aneurysms: Ten Years of Lessons Learned and Adjustments in Practice from the WorldWideWEB Consortium - Adam A. Dmytriw; Mahmoud Dibas; Sherief Ghozy; Nimer Adeeb; Jose Danilo Bengzon Diestro; Kevin Phan; Hugo H. Cuellar-Saenz; Ahmad Sweid; Sovann V. Lay; Adrien Guenego; Leonardo Renieri; Ali Al Balushi; et al. (Translational Stroke Research, 2023)

Technological innovations to reduce the impact of bottom gears on the seabed - Antonello Sala; Jochen Depestele; Aysun Gümüş; Pascal Laffargue; J. Rasmus Nielsen; Hans Polet; Chris J. Smith; Mustafa Zengin; Francois Bastardie; Ole R. Eigaard; Katell G. Hamon; Frank Jensen; et al. (Marine Policy, 2023)

Bacterial adaptation to cold: Conservation of a short J‐domain co‐chaperone and its protein partners in environmental proteobacteria - Lana Weber; Atar Gilat; Nathanael Maillot; Deborah Byrne; Pascal Arnoux; Marie‐Thérèse Giudici‐Orticoni; Vincent Méjean; Marianne Ilbert; Olivier Genest; Rina Rosenzweig; Sébastien Dementin (Environmental Microbiology, 2023)
Bacterial genomes are a huge reservoir of genes encoding J‐domain protein co‐chaperones that recruit the molecular chaperone DnaK to assist protein substrates involved in survival, adaptation, or fitness. The atc operon of the aquatic mesophilic bacterium Shewanella oneidensis encodes the proteins AtcJ, AtcA, AtcB, and AtcC, and all of them, except AtcA, are required for growth at low temperatures. AtcJ is a short J‐domain protein that interacts with DnaK, but also with AtcC through its 21 amino acid C‐terminal domain. This interaction network is critical for cold growth. Here, we show that AtcJ represents a subfamily of short J‐domain proteins that (i) are found in several environmental, mostly aquatic, β‐ or ɣ‐proteobacteria and (ii) contain a conserved PX 7 W motif in their C‐terminal extension. Using a combination of NMR, biochemical and genetic approaches, we show that the hydrophobic nature of the tryptophan of the S. oneidensis AtcJ PX 7 W motif determines the strong AtcJ–AtcC interaction essential for cold growth. The AtcJ homologues are encoded by operons containing at least the S. oneidensis atcA , atcB , and atcC homologues. These findings suggest a conserved network of DnaK and Atc proteins necessary for low‐temperature growth and, given the variation in the atc operons, possibly for other biological functions.

The Woven EndoBridge (WEB) Device for the Treatment of Intracranial Aneurysms: Ten Years of Lessons Learned and Adjustments in Practice from the WorldWideWEB Consortium - Adam A. Dmytriw; Mahmoud Dibas; Sherief Ghozy; Nimer Adeeb; Jose Danilo Bengzon Diestro; Kevin Phan; Hugo H. Cuellar-Saenz; Ahmad Sweid; Sovann V. Lay; Adrien Guenego; Leonardo Renieri; Ali Al Balushi; et al. (Translational Stroke Research, 2023)

Challenges related to the application of analytical methods to control insect meals in the context of European legislation - Abigaël Anselmo; Pascal Veys; Olivier Fumière; Marie-Caroline Lecrenier; Alexandra Cordonnier; Denis Michez; Vincent Baeten (Food Additives & Contaminants: Part A, 2023)

Termite constructions as patches of soil fertility in Cambodian paddy fields - Ratha Muon; Pinnara Ket; David Sebag; Hanane Aroui Boukbida; Pascal Podwojewski; Vincent Hervé; Vannak Ann; Pascal Jouquet (Geoderma Regional, 2023)

Data quality control considerations in multivariate environmental monitoring: experience of the French coastal network SOMLIT - Elsa Breton; Nicolas Savoye; Peggy Rimmelin-Maury; Benoit Sautour; Eric Goberville; Arnaud Lheureux; Thierry Cariou; Sophie Ferreira; Hélène Agogué; Samir Alliouane; Fabien Aubert; Sébastien Aubin; et al. (Frontiers in Marine Science, 2023)
Introduction While crucial to ensuring the production of accurate and high-quality data—and to avoid erroneous conclusions—data quality control (QC) in environmental monitoring datasets is still poorly documented. Methods With a focus on annual inter-laboratory comparison (ILC) exercises performed in the context of the French coastal monitoring SOMLIT network, we share here a pragmatic approach to QC, which allows the calculation of systematic and random errors, measurement uncertainty, and individual performance. After an overview of the different QC actions applied to fulfill requirements for quality and competence, we report equipment, accommodation, design of the ILC exercises, and statistical methodology specially adapted to small environmental networks (<20 laboratories) and multivariate datasets. Finally, the expanded uncertainty of measurement for 20 environmental variables routinely measured by SOMLIT from discrete sampling—including Essential Ocean Variables—is provided. Results, Discussion, Conclusion The examination of the temporal variations (2001–2021) in the repeatability, reproducibility, and trueness of the SOMLIT network over time confirms the essential role of ILC exercises as a tool for the continuous improvement of data quality in environmental monitoring datasets.

Interplay of regio-selectively modified dendritic silica particles with styrene-butadiene rubber: The route towards better tires with lower rolling-resistance and higher grip - Enzo Moretto; Charlotte Stoffels; Carlos Eloy Federico; Vincent Rogé; Mariapaola Staropoli; Iikpoemugh Elo Imiete; Jean-Nicolas Audinot; Pascal Steiner; Benoît Duez; Damien Lenoble; Jean-Sébastien Thomann (Chemical Engineering Journal, 2023)

Temporal pesticide dynamics alter specific eukaryotic taxa in a coastal transition zone - Vincent Hervé; Pierre Sabatier; Josie Lambourdière; Jérôme Poulenard; Pascal Jean Lopez (Science of The Total Environment, 2023)

Trajectories of nutrients concentrations and ratios in the French coastal ecosystems: 20 years of changes in relation with large-scale and local drivers - Arnaud Lheureux; Valérie David; Yolanda Del Amo; Dominique Soudant; Isabelle Auby; Yann Bozec; Pascal Conan; Florian Ganthy; Gérald Grégori; Alain Lefebvre; Aude Leynart; Peggy Rimmelin-Maury; et al. (Science of The Total Environment, 2023)

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Impact of bacterial strain acquisition in the lung of patients with COPD: the AERIS study - Lucio Malvisi; Aparna Yarraguntla; Marie-Cécile Mortier; Karen Osman; David W. Cleary; Béatrice Sente; Thierry G. Pascal; Vincent Weynants; Stuart C. Clarke; Laura Taddei; Tom M. A. Wilkinson; Jeanne-Marie Devaster; et al. (Infectious Diseases, 2022)

Mechanism of Cellular Formation and In Vivo Seeding Effects of Hexameric β-Amyloid Assemblies - Céline Vrancx; Devkee M. Vadukul; Nuria Suelves; Sabrina Contino; Ludovic D’Auria; Florian Perrin; Vincent van Pesch; Bernard Hanseeuw; Loïc Quinton; Pascal Kienlen-Campard (Molecular Neurobiology, 2021)
The β-amyloid peptide (Aβ) is found as amyloid fibrils in senile plaques, a typical hallmark of Alzheimer’s disease (AD). However, intermediate soluble oligomers of Aβ are now recognized as initiators of the pathogenic cascade leading to AD. Studies using recombinant Aβ have shown that hexameric Aβ in particular acts as a critical nucleus for Aβ self-assembly. We recently isolated hexameric Aβ assemblies from a cellular model, and demonstrated their ability to enhance Aβ aggregation in vitro. Here, we report the presence of similar hexameric-like Aβ assemblies across several cellular models, including neuronal-like cell lines. In order to better understand how they are produced in a cellular context, we investigated the role of presenilin-1 (PS1) and presenilin-2 (PS2) in their formation. PS1 and PS2 are the catalytic subunits of the γ-secretase complex that generates Aβ. Using CRISPR-Cas9 to knockdown each of the two presenilins in neuronal-like cell lines, we observed a direct link between the PS2-dependent processing pathway and the release of hexameric-like Aβ assemblies in extracellular vesicles. Further, we assessed the contribution of hexameric Aβ to the development of amyloid pathology. We report the early presence of hexameric-like Aβ assemblies in both transgenic mice brains exhibiting human Aβ pathology and in the cerebrospinal fluid of AD patients, suggesting hexameric Aβ as a potential early AD biomarker. Finally, cell-derived hexameric Aβ was found to seed other human Aβ forms, resulting in the aggravation of amyloid deposition in vivo and neuronal toxicity in vitro.

Structure of genetic diversity and genome-wide association studies of bean fly (Ophiomyia spencerella) resistance in common bean - Pascal P. Okwiri Ojwang; Tilly Eldridge; Pilar Corredor-Moreno; Vincent Njung’e (Euphytica, 2021)
Eastern Africa is a significant region of common bean ( Phaseolus vulgaris L.) production and genetic diversity. Insect pests are a major biotic constraint in subsistence crop production systems. Bean fly ( Ophiomyia spencerella ) is a serious pest of beans in eastern Africa highlands. Breeding efforts focus on combining adaptability traits with user preferred seed types. However, lack of information on molecular markers linked to genes modulating bean fly resistance has slowed breeding progress. The objectives were to: (i) characterize genetic diversity and uncover putative bean fly resistant genotypes within diverse seed types and market classes and (ii) identify genomic regions controlling bean fly resistance using genome-wide association analysis (GWAS). A set of 276 diverse genotypes comprising local landraces and varieties from Kenya alongside introductions from International Centre for Tropical Agriculture (CIAT), were assembled. The germplasm represented varied bean production ecologies and seed types. Genetic diversity conforming to Andean and Mesoamerican genepools was established. Out of 276 genotypes evaluated, 150 were Andean, 74 were Mesoamerican and 52 were admixed. Twenty-two genotypes were resistant to bean fly. Association mapping results for stem damage score and plant mortality identified six significant single-nucleotide polymorphisms (SNPs) on chromosomes Pv01 and Pv09. The most significant SNP marker was 12 kilobases downstream of Phvul.001G074900 gene with LOD score > 4.0 hence in linkage disequilibrium with the postulated gene. The identified candidate gene is pleiotropic and modulates both flowering time and plant responses to stress. These findings are a key step towards marker-enabled breeding in common bean for sub-Saharan Africa.

ddPCR increases detection of SARS-CoV-2 RNA in patients with low viral loads - Agnès Marchio; Christophe Batejat; Jessica Vanhomwegen; Maxence Feher; Quentin Grassin; Maxime Chazal; Olivia Raulin; Anne Farges-Berth; Florence Reibel; Vincent Estève; Anne Dejean; Nolwenn Jouvenet; et al. (Archives of Virology, 2021)
RT-qPCR detection of SARS-CoV-2 RNA still represents the method of reference to diagnose and monitor COVID-19. From the onset of the pandemic, however, doubts have been expressed concerning the sensitivity of this molecular diagnosis method. Droplet digital PCR (ddPCR) is a third-generation PCR technique that is particularly adapted to detecting low-abundance targets. We developed two-color ddPCR assays for the detection of four different regions of SARS-CoV-2 RNA, including non-structural (IP4-RdRP, helicase) and structural (E, N) protein-encoding sequences. We observed that N or E subgenomic RNAs are generally more abundant than IP4 and helicase RNA sequences in cells infected in vitro , suggesting that detection of the N gene, coding for the most abundant subgenomic RNA of SARS-CoV-2, increases the sensitivity of detection during the highly replicative phase of infection. We investigated 208 nasopharyngeal swabs sampled in March-April 2020 in different hospitals of Greater Paris. We found that 8.6% of informative samples (n = 16/185, P

Which Method for Which Purpose? A Comparison of Line Intercept Transect and Underwater Photogrammetry Methods for Coral Reef Surveys - Isabel Urbina-Barreto; Rémi Garnier; Simon Elise; Romain Pinel; Pascal Dumas; Vincent Mahamadaly; Mathilde Facon; Sophie Bureau; Christophe Peignon; Jean-Pascal Quod; Eric Dutrieux; Lucie Penin; et al. (Frontiers in Marine Science, 2021)
The choice of ecological monitoring methods and descriptors determines the effectiveness of a program designed to assess the state of coral reef ecosystems. Here, we comparer the relative performance of the traditional Line Intercept Transect (LIT) method with three methods derived from underwater photogrammetry: LIT on orthomosaics, photoquadrats from orthomosaics, and surface analyses on orthomosaics. The data were acquired at Reunion Island on five outer reef slopes and two coral communities on underwater lava-flows. Coral cover was estimated in situ using the LIT method and with LITs and photoquadrats digitized on orthomosaic. Surface analyses were done on the same orthomosaics. Structural complexity of the surveyed sites was calculated from digital elevation models using three physical descriptors (fractal dimension, slope, surface complexity), and used to explore their possible influence in coral cover estimates. We also compared the methods in terms of scientific outputs, the human expertise and time required. Coral cover estimates obtained with in situ LITs were higher than those obtained with digitized LITs and photoquadrats. Surfaces analyses on orthomosaics yielded the lowest but most the precise cover estimates (i.e., lowest sample dispersion). Sites with the highest coral cover also had the highest structural complexity. Finally, when we added scientific outputs, and requirements for human expertise and time to our comparisons between methods, we found that surface analysis on the orthomosaics was the most efficient method. Photoquadrats were more time-consuming than both in situ and digitized LITs, even though they provided coral cover estimates similar to those of digitized LITs and yielded more than one descriptor. The LIT in situ method remains the least time-consuming and most effective for species-level taxonomic identifications but is the most limited method in terms of data outputs and representativeness of the ecosystem.

Seasonal and Interannual Variability of the CO2 System in the Eastern Mediterranean Sea: A Case Study in the North Western Levantine Basin - Cathy Wimart-Rousseau; Thibaut Wagener; Marta Álvarez; Thierry Moutin; Marine Fourrier; Laurent Coppola; Laure Niclas-Chirurgien; Patrick Raimbault; Fabrizio D’Ortenzio; Xavier Durrieu de Madron; Vincent Taillandier; Franck Dumas; et al. (Frontiers in Marine Science, 2021)
The seasonal variability of the carbonate system in the eastern Mediterranean Sea (EMed) was investigated based on discrete total alkalinity (A T ), total dissolved inorganic carbon (C T ), and pH measurements collected during three cruises around Crete between June 2018 and March 2019. This study presents a detailed description of this new carbonate chemistry dataset in the eastern Mediterranean Sea. We show that the North Western Levantine Basin (NWLB) is unique in terms of range of A T variation vs. C T variation in the upper water column over an annual cycle. The reasons for this singularity of the NWLB can be explained by the interplay between strong evaporation and the concomitant consumption of C T by autotrophic processes. The high range of A T variations, combined to temperature changes, has a strong impact on the variability of the seawater p CO 2 ( p CO 2 S W ). Based on Argo float data, an entire annual cycle for p CO 2 S W in the NWLB has been reconstructed in order to estimate the temporal sequence of the potential “source” and “sink” of atmospheric CO 2 . By combining this dataset with previous observations in the NWLB, this study shows a significant ocean acidification and a decrease in the oceanic surface pH T 25 of −0.0024 ± 0.0004 pH T 25 units.a –1 . The changes in the carbonate system are driven by the increase of atmospheric CO 2 but also by unexplained temporal changes in the surface A T content. If we consider that the EMed will, in the future, encounter longer, more intense and warmer summer seasons, this study proposes some perspectives on the carbonate system functioning of the “future” EMed.

In silico and in vitro screening of licensed antimalarial drugs for repurposing as inhibitors of hepatitis E virus - Borris Rosnay Tietcheu Galani; Vincent Brice Ayissi Owona; Romeo Joel Guemmogne Temdie; Karoline Metzger; Marie Atsama Amougou; Pascal Dieudonné Djamen Chuisseu; Arnaud Fondjo Kouam; Marceline Ngounoue Djuidje; Cécile-Marie Aliouat-Denis; Laurence Cocquerel; Paul Fewou Moundipa (In Silico Pharmacology, 2021)

Pyruvate dehydrogenase kinase/lactate axis: a therapeutic target for neovascular age-related macular degeneration identified by metabolomics - Vincent Lambert; Sylvain Hansen; Matthieu Schoumacher; Julie Lecomte; Justine Leenders; Pascale Hubert; Michael Herfs; Silvia Blacher; Oriane Carnet; Cassandre Yip; Pierre Blaise; Edouard Duchateau; et al. (Journal of Molecular Medicine, 2020)

Staphylococcus capitis isolated from bloodstream infections: a nationwide 3-month survey in 38 neonatal intensive care units - Marie Decalonne; Sandra Dos Santos; Rémi Gimenes; Florent Goube; Géraldine Abadie; Saïd Aberrane; Vanina Ambrogi; Raoul Baron; Patrick Barthelemy; Isabelle Bauvin; Olivier Belmonte; Emilie Benabid; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)
To increase the knowledge about S. capitis in the neonatal setting, we conducted a nationwide 3-month survey in 38 neonatal intensive care units (NICUs) covering 56.6% of French NICU beds. We demonstrated 14.2% of S. capitis BSI ( S.cap BSI) among nosocomial BSIs. S.cap BSI incidence rate was 0.59 per 1000 patient-days. A total of 55.0% of the S.cap BSIs were late onset catheter-related BSIs. The S. capitis strains infected preterm babies (median gestational age 26 weeks, median birth weight 855 g). They were resistant to methicillin and aminoglycosides and belonged to the NRCS-A clone. Evolution was favorable in all but one case, following vancomycin treatment.

Satellite and In Situ Monitoring of Chl-a, Turbidity, and Total Suspended Matter in Coastal Waters: Experience of the Year 2017 along the French Coasts - Francis Gohin; Philippe Bryère; Alain Lefebvre; Pierre-Guy Sauriau; Nicolas Savoye; Vincent Vantrepotte; Yann Bozec; Thierry Cariou; Pascal Conan; Sylvain Coudray; Gaelle Courtay; Sylvaine Françoise; et al. (Journal of Marine Science and Engineering, 2020)
The consistency of satellite and in situ time series of Chlorophyll-a (Chl-a), Turbidity and Total Suspended Matters (TSM) was investigated at 17 coastal stations throughout the year 2017. These stations covered different water types, from relatively clear waters in the Mediterranean Sea to moderately turbid regions in the Bay of Biscay and the southern bight of the North-Sea. Satellite retrievals were derived from MODIS/AQUA, VIIRS/NPP and OLCI-A/Sentinel-3 spectral reflectance. In situ data were obtained from the coastal phytoplankton networks SOMLIT (CNRS), REPHY (Ifremer) and associated networks. Satellite and in situ retrievals of the year 2017 were compared to the historical seasonal cycles and percentiles, 10 and 90, observed in situ. Regarding the sampling frequency in the Mediterranean Sea, a weekly in situ sampling allowed all major peaks in Chl-a caught from space to be recorded at sea, and, conversely, all in situ peaks were observed from space in a frequently cloud-free atmosphere. In waters of the Eastern English Channel, lower levels of Chl-a were observed, both in situ and from space, compared to the historical averages. However, despite a good overall agreement for low to moderate biomass, the satellite method, based on blue and green wavelengths, tends to provide elevated and variable Chl-a in a high biomass environment. Satellite-derived TSM and Turbidity were quite consistent with in situ measurements. Moreover, satellite retrievals of the water clarity parameters often showed a lower range of variability than their in situ counterparts did, being less scattered above and under the seasonal curves of percentiles 10 and 90.

Tree species diversity improves beech growth and alters its physiological response to drought - Astrid Vannoppen; Kerstin Treydte; Pascal Boeckx; Vincent Kint; Quentin Ponette; Kris Verheyen; Bart Muys (Trees, 2020)

Mutations in aARS genes revealed by targeted next-generation sequencing in patients with mitochondrial diseases - Rahma Felhi; Majida Charif; Lamia Sfaihi; Emna Mkaouar-Rebai; Valerie Desquiret-Dumas; Rim Kallel; Céline Bris; David Goudenège; Agnès Guichet; Dominique Bonneau; Vincent Procaccio; Pascal Reynier; et al. (Molecular Biology Reports, 2020)

Analysis of interdomain taxonomic patterns in urban street mats - Vincent Hervé; Pascal Jean Lopez (Environmental Microbiology, 2020)
Summary Streets are constantly crossed by billions of vehicles and pedestrians. Their gutters, which convey stormwater and contribute to waste management, and are important for human health and well‐being, probably play a number of ecological roles. Street surfaces may also represent an important part of city surface areas. To better characterize the ecology of this yet poorly explored compartment, we used filtration and DNA metabarcoding to address microbial community composition and assembly across the city of Paris, France. Diverse bacterial and eukaryotic taxonomic groups were identified, including members involved in key biogeochemical processes, along with a number of parasites and putative pathogens of human, animals and plants. We showed that the beta diversity patterns between bacterial and eukaryotic communities were correlated, suggesting interdomain associations. Beta diversity analyses revealed the significance of biotic factors (cohesion metrics) in shaping gutter microbial community assembly and, to a lesser extent, the contribution of abiotic factors (pH and conductivity). Co‐occurrences analysis confirmed contrasting non‐random patterns both within and between domains of life, specifically when comparing diatoms and fungi. Our results highlight microbial coexistence patterns in streets and reinforce the need to further explore biodiversity in urban ground transportation infrastructures.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Long‐term influence of early human occupations on current forests of the Guiana Shield - Guillaume Odonne; Martijn van den Bel; Maxime Burst; Olivier Brunaux; Miléna Bruno; Etienne Dambrine; Damien Davy; Mathilde Desprez; Julien Engel; Bruno Ferry; Vincent Freycon; Pierre Grenand; et al. (Ecology, 2019)
To decipher the long‐term influences of pre‐Columbian land occupations on contemporary forest structure, diversity, and functioning in Amazonia, most of the previous research focused on the alluvial plains of the major rivers of the Amazon basin. Terra firme, that is, nonflooded forests, particularly from the Guiana Shield, are yet to be explored. In this study, we aim to give new insights into the subtle traces of pre‐Columbian influences on present‐day forests given the archaeological context of terra firme forests of the Guiana Shield. Following archaeological prospects on 13 sites in French Guiana, we carried out forest inventories inside and outside archaeological sites and assessed the potential pre‐Columbian use of the sampled tree species using an original ethnobotanical database of the Guiana Shield region. Aboveground biomass (320 and 380 T/ha, respectively), basal area (25–30 and 30–35 m 2 /ha, respectively), and tree density (550 and 700 stem/ha, respectively) were all significantly lower on anthropized plots (As) than on nonanthropized plots ( NA s). Ancient human presence shaped the species composition of the sampled forests with Arecaceae, Burseraceae, and Lauraceae significantly more frequent in As and Annonaceae and Lecythidaceae more frequent in NA s. Although alpha diversity was not different between As and NA s, the presence of pre‐Columbian sites enhances significantly the forest beta diversity at the landscape level. Finally, trees with edible fruits are positively associated with pre‐Columbian sites, whereas trees used for construction or for their bark are negatively associated with pre‐Columbian sites. Half a millennium after their abandonment, former occupied places from the inner Guiana Shield still bear noticeable differences with nonanthropized places. Considering the lack of data concerning archaeology of terra firme Amazonian forests, our results suggest that pre‐Columbian influences on the structure (lower current biomass), diversity (higher beta diversity), and composition (linked to the past human tree uses) of current Amazonian forests might be more important than previously thought.

Combining multiple visual surveys to model the habitat of deep‐diving cetaceans at the basin scale - Auriane Virgili; Matthieu Authier; Oliver Boisseau; Ana Cañadas; Diane Claridge; Tim Cole; Peter Corkeron; Ghislain Dorémus; Léa David; Nathalie Di‐Méglio; Charlotte Dunn; Tim E. Dunn; et al. (Global Ecology and Biogeography, 2019)
Aim Deep‐diving cetaceans are oceanic species exposed to multiple anthropogenic pressures including high intensity underwater noise, and knowledge of their distribution is crucial to manage their conservation. Due to intrinsic low densities, wide distribution ranges and limited presence at the sea surface, these species are rarely sighted. Pooling data from multiple visual surveys sharing a common line‐transect methodology can increase sightings but requires accounting for heterogeneity in protocols and platforms. Location North Atlantic Ocean and Mediterranean Sea. Time period 1998 to 2015. Major taxa Ziphiidae; Physeteriidae; Kogiidae. Methods About 1,240,000 km of pooled effort provided 630 sightings of ziphiids, 836 of physeteriids and 106 of kogiids. For each taxon, we built a hierarchical model to estimate the effective strip width depending on observation conditions and survey types. We then modelled relative densities in a generalized additive modelling framework. Geographical predictions were limited to interpolations identified with a gap analysis of environmental space coverage. Results Deeper areas of the North Atlantic gyre were mostly environmental extrapolation in the predictions, thereby highlighting gaps in sampling across the different surveys. For the three species groups, the highest relative densities were predicted along continental slopes, particularly in the western North Atlantic Ocean where the Gulf Stream creates dynamic frontal zones and eddies. Main conclusions Pooling a large number of surveys provided the first basin‐wide models of distribution for deep‐diving cetaceans, including several data‐deficient taxa, across the North Atlantic Ocean and the Mediterranean Sea. These models can help the conservation of elusive and poorly known marine megafauna.

Impact of Geological Heterogeneities on Induced-Seismicity in a Deep Sublevel Stoping Mine - Francesca De Santis; Isabelle Contrucci; Jannes Kinscher; Pascal Bernard; Vincent Renaud; Yann Gunzburger (Pure and Applied Geophysics, 2019)

Compositional response of Amazon forests to climate change - Adriane Esquivel‐Muelbert; Timothy R. Baker; Kyle G. Dexter; Simon L. Lewis; Roel J. W. Brienen; Ted R. Feldpausch; Jon Lloyd; Abel Monteagudo‐Mendoza; Luzmila Arroyo; Esteban Álvarez-Dávila; Niro Higuchi; Beatriz S. Marimon; et al. (Global Change Biology, 2019)
Most of the planet's diversity is concentrated in the tropics, which includes many regions undergoing rapid climate change. Yet, while climate‐induced biodiversity changes are widely documented elsewhere, few studies have addressed this issue for lowland tropical ecosystems. Here we investigate whether the floristic and functional composition of intact lowland Amazonian forests have been changing by evaluating records from 106 long‐term inventory plots spanning 30 years. We analyse three traits that have been hypothesized to respond to different environmental drivers (increase in moisture stress and atmospheric CO 2 concentrations): maximum tree size, biogeographic water‐deficit affiliation and wood density. Tree communities have become increasingly dominated by large‐statured taxa, but to date there has been no detectable change in mean wood density or water deficit affiliation at the community level, despite most forest plots having experienced an intensification of the dry season. However, among newly recruited trees, dry‐affiliated genera have become more abundant, while the mortality of wet‐affiliated genera has increased in those plots where the dry season has intensified most. Thus, a slow shift to a more dry‐affiliated Amazonia is underway, with changes in compositional dynamics (recruits and mortality) consistent with climate‐change drivers, but yet to significantly impact whole‐community composition. The Amazon observational record suggests that the increase in atmospheric CO 2 is driving a shift within tree communities to large‐statured species and that climate changes to date will impact forest composition, but long generation times of tropical trees mean that biodiversity change is lagging behind climate change.

Herpes simplex encephalitis relapse associated with positive N-methyl-d-aspartate receptor antibodies - Sabina Boangher; Pascal Mespouille; Sophie Goffette; Vincent van Pesch; Dan Cuciureanu (Acta Neurologica Belgica, 2018)

Pan‐tropical prediction of forest structure from the largest trees - Jean‐François Bastin; Ervan Rutishauser; James R. Kellner; Sassan Saatchi; Raphael Pélissier; Bruno Hérault; Ferry Slik; Jan Bogaert; Charles De Cannière; Andrew R. Marshall; John Poulsen; Patricia Alvarez‐Loyayza; et al. (Global Ecology and Biogeography, 2018)
Aim Large tropical trees form the interface between ground and airborne observations, offering a unique opportunity to capture forest properties remotely and to investigate their variations on broad scales. However, despite rapid development of metrics to characterize the forest canopy from remotely sensed data, a gap remains between aerial and field inventories. To close this gap, we propose a new pan‐tropical model to predict plot‐level forest structure properties and biomass from only the largest trees. Location Pan‐tropical. Time period Early 21st century. Major taxa studied Woody plants. Methods Using a dataset of 867 plots distributed among 118 sites across the tropics, we tested the prediction of the quadratic mean diameter, basal area, Lorey's height, community wood density and aboveground biomass (AGB) from the i th largest trees. Results Measuring the largest trees in tropical forests enables unbiased predictions of plot‐ and site‐level forest structure. The 20 largest trees per hectare predicted quadratic mean diameter, basal area, Lorey's height, community wood density and AGB with 12, 16, 4, 4 and 17.7% of relative error, respectively. Most of the remaining error in biomass prediction is driven by differences in the proportion of total biomass held in medium‐sized trees (50–70 cm diameter at breast height), which shows some continental dependency, with American tropical forests presenting the highest proportion of total biomass in these intermediate‐diameter classes relative to other continents. Main conclusions Our approach provides new information on tropical forest structure and can be used to generate accurate field estimates of tropical forest carbon stocks to support the calibration and validation of current and forthcoming space missions. It will reduce the cost of field inventories and contribute to scientific understanding of tropical forest ecosystems and response to climate change.

Eddy properties in the Southern California Current System - Fanny Chenillat; Peter J. S. Franks; Xavier Capet; Pascal Rivière; Nicolas Grima; Bruno Blanke; Vincent Combes (Ocean Dynamics, 2018)

Evolution of a beach nourishment project using dredged sand from navigation channel, Dunkirk, northern France - Alexandra Spodar; Arnaud Héquette; Marie-Hélène Ruz; Adrien Cartier; Pascal Grégoire; Vincent Sipka; Nicolas Forain (Journal of Coastal Conservation, 2018)

Nest design in a changing world: Great tit Parus major nests from a Mediterranean city environment as a case study - Marcel M. Lambrechts; Anne Charmantier; Virginie Demeyrier; Annick Lucas; Samuel Perret; Matthieu Abouladzé; Michel Bonnet; Coline Canonne; Virginie Faucon; Stéphanie Grosset; Gaëlle le Prado; Frédéric Lidon; et al. (Urban Ecosystems, 2017)

Collaborative study on the effect of grinding on the detection of bones from processed animal proteins in feed by light microscopy - Pascal Veys; Viviane Planchon; Ruairi Colbert; Clara Cruz; Geneviève Frick; Ioannis Ioannou; Daniela Marchis; Erik Nordkvist; Inge Paradies-Severin; Arja Pohto; Roland Weiss; Vincent Baeten; et al. (Food Additives & Contaminants: Part A, 2017)

Light microscopy with differential staining techniques for the characterisation and discrimination of insects versus marine arthropods processed animal proteins - Matteo Ottoboni; Marco Tretola; Federica Cheli; Daniela Marchis; Pascal Veys; Vincent Baeten; Luciano Pinotti (Food Additives & Contaminants: Part A, 2017)

Coming Full Circle: Why Social and Institutional Dimensions Matter for the Circular Economy - Vincent Moreau; Marlyne Sahakian; Pascal van Griethuysen; François Vuille (Journal of Industrial Ecology, 2017)
Summary In light of the environmental consequences of linear production and consumption processes, the circular economy (CE) is gaining momentum as a concept and practice, promoting closed material cycles by focusing on multiple strategies from material recycling to product reuse, as well as rethinking production and consumption chains toward increased resource efficiency. Yet, by considering mainly cost‐effective opportunities within the realm of economic competitiveness, it stops short of grappling with the institutional and social predispositions necessary for societal transitions to a CE. The distinction of noncompetitive and not‐for‐profit activities remains to be addressed, along with other societal questions relating to labor conditions, wealth distribution, and governance systems. In this article, we recall some underlying biophysical aspects to explain the limits to current CE approaches. We examine the CE from a biophysical and social perspective to show that the concept lacks the social and institutional dimensions to address the current material and energy throughput in the economy. We show that reconsidering labor is essential to tackling the large share of dissipated material and energy flows that cannot be recovered economically. Institutional conditions have an essential role to play in setting the rules that differentiate profitable from nonprofitable activities. In this context, the social and solidarity economy, with its focus on equity with respect to labor and governance, provides an instructive and practical example that defies the constraints related to current institutional conditions and economic efficiency. We show how insights from the principles of the social and solidarity economy can contribute to the development of a CE by further defining who bears the costs of economic activities.

Influence of bottom trawling on sediment resuspension in the ‘Grande-Vasière’ area (Bay of Biscay, France) - Baptiste Mengual; Florence Cayocca; Pierre Le Hir; Robin Draye; Pascal Laffargue; Benoit Vincent; Thierry Garlan (Ocean Dynamics, 2016)

Early relapse with tumefactive MS lesion upon initiation of fingolimod therapy - Sabina Boangher; Sophie Goffette; Vincent Van Pesch; Pascal Mespouille (Acta Neurologica Belgica, 2016)

Extrapolating cetacean densities beyond surveyed regions: habitat‐based predictions in the circumtropical belt - Laura Mannocci; Pascal Monestiez; Jérôme Spitz; Vincent Ridoux (Journal of Biogeography, 2015)
Aim Our knowledge of cetacean distributions is impeded by large data‐gaps worldwide, particularly at tropical latitudes. This study aims to (1) find generic relationships between cetaceans and their habitats in a range of tropical waters, and (2) extrapolate cetacean densities in a circumtropical belt extending far beyond surveyed regions. Location Pelagic, circumtropical. Methods Aerial surveys were conducted over three regions in the tropical Atlantic (132,000 km 2 ), Indian (1.4 million km 2 ) and Pacific (1.4 million km 2 ) oceans. Three cetacean guilds were studied (Delphininae, Globicephalinae and sperm and beaked whales). For each guild, a generalized additive model was fitted using sightings recorded in all three regions and 14 candidate environmental predictors. Cetacean densities were tentatively extrapolated over a circumtropical belt, excluding waters where environmental characteristics departed from those encountered in the surveyed regions. Results Each cetacean guild exhibited a relationship with the primary production and depth of the minimum dissolved oxygen concentration. Delphininae also showed a relationship with the dominant phytoplankton group. The prediction envelopes were primarily constrained by water temperature. Circumtropical extrapolations of Delphininae and Globicephalinae were contrasted between ocean basins, with high densities predicted in the equatorial waters of the three ocean basins. The predicted densities of sperm and beaked whales were lower and more uniform across the circumtropical belt than for the other two guilds. Main conclusions Our modelling approach represents a good analytical solution to predicting cetacean population densities in poorly documented tropical waters. Future data collection should concentrate on areas where environmental characteristics were not encountered in our survey regions and where the predicted densities were the most uncertain. By highlighting cetacean hotspots far beyond waters under national jurisdiction, this study can provide guidance for the delimitation of Ecologically and Biologically Significant Marine Areas.

Spatial leave‐one‐out cross‐validation for variable selection in the presence of spatial autocorrelation - Kévin Le Rest; David Pinaud; Pascal Monestiez; Joël Chadoeuf; Vincent Bretagnolle (Global Ecology and Biogeography, 2014)
Aim Processes and variables measured in ecology are almost always spatially autocorrelated, potentially leading to the choice of overly complex models when performing variable selection. One way to solve this problem is to account for residual spatial autocorrelation ( RSA ) for each subset of variables considered and then use a classical model selection criterion such as the A kaike information criterion ( AIC ). However, this method can be laborious and it raises other concerns such as which spatial model to use or how to compare different spatial models. To improve the accuracy of variable selection in ecology, this study evaluates an alternative method based on a spatial cross‐validation procedure. Such a procedure is usually used for model evaluation but can also provide interesting outcomes for variable selection in the presence of spatial autocorrelation. Innovation We propose to use a special case of spatial cross‐validation, spatial leave‐one‐out ( SLOO ), giving a criterion equivalent to the AIC in the absence of spatial autocorrelation. SLOO only computes non‐spatial models and uses a threshold distance (equal to the range of RSA ) to keep each point left out spatially independent from the others. We first provide some simulations to evaluate how SLOO performs compared with AIC . We then assess the robustness of SLOO on a large‐scale dataset. R software codes are provided for generalized linear models. Main conclusions The AIC was relevant for variable selection in the presence of RSA if the independent variables considered were not spatially autocorrelated. It otherwise failed because highly spatially autocorrelated variables were more often selected than others. Conversely, SLOO had similar performances whether the variables were themselves spatially autocorrelated or not. It was particularly useful when the range of RSA was small, which is a common property of spatial tools. SLOO appears to be a promising solution for selecting relevant variables from most ecological spatial datasets.

Invasive Geotrichum clavatum Fungal Infection in an Acute Myeloid Leukaemia Patient: A Case Report and Review - Vincent Camus; Marie-Laure Thibault; Marion David; Gilles Gargala; Patricia Compagnon; Fabien Lamoureux; Christophe Girault; Jean-Baptiste Michot; Aspasia Stamatoullas; Hélène Lanic; Fabrice Jardin; Pascal Lenain; et al. (Mycopathologia, 2014)

Molecular Imaging of Cerebrovascular Lesions - Nohra Chalouhi; Pascal Jabbour; Vincent Magnotta; David Hasan (Translational Stroke Research, 2014)

Advancing climate compatible development: lessons from southern Africa - Lindsay C. Stringer; Andrew J. Dougill; Jen C. Dyer; Katharine Vincent; Florian Fritzsche; Julia Leventon; Mario Paulo Falcão; Pascal Manyakaidze; Stephen Syampungani; Philip Powell; Gabriel Kalaba (Regional Environmental Change, 2014)

Prediction of water temperature heterogeneity of braided rivers using very high resolution thermal infrared (TIR) images - Vincent Wawrzyniak; Hervé Piégay; Pascal Allemand; Lise Vaudor; Philippe Grandjean (International Journal of Remote Sensing, 2013)

Impacts of species interactions on grass community productivity under contrasting management regimes - Laíse da Silveira Pontes; Vincent Maire; Frédérique Louault; Jean-François Soussana; Pascal Carrère (Oecologia, 2012)

Food web analysis in intertidal Zostera marina and Zostera noltii communities in winter and summer - Vincent Ouisse; Pascal Riera; Aline Migné; Cédric Leroux; Dominique Davoult (Marine Biology, 2012)

Identification of mediator complex 26 (Crsp7) gametologs on platypus X1 and Y5 sex chromosomes: a candidate testis-determining gene in monotremes? - Enkhjargal Tsend-Ayush; R. Daniel Kortschak; Pascal Bernard; Shu Ly Lim; Janelle Ryan; Ruben Rosenkranz; Tatiana Borodina; Juliane C. Dohm; Heinz Himmelbauer; Vincent R. Harley; Frank Grützner (Chromosome Research, 2012)

Sox9 gene regulation and the loss of the XY/XX sex-determining mechanism in the mole vole Ellobius lutescens - Stefan Bagheri-Fam; Rajini Sreenivasan; Pascal Bernard; Kevin C. Knower; Ryohei Sekido; Robin Lovell-Badge; Walter Just; Vincent R. Harley (Chromosome Research, 2012)

Fine sediments as a granular source for civil engineering - Vincent Dubois; Rachid Zentar; Nor-Edine Abriak; Pascal Grégoire (European Journal of Environmental and Civil Engineering, 2011)

Roughness of simulated surfaces examined with a haptic tool: effects of spatial period, friction, and resistance amplitude - Allan M. Smith; Georges Basile; Jonathan Theriault-Groom; Pascal Fortier-Poisson; Gianni Campion; Vincent Hayward (Experimental Brain Research, 2010)

Peptide Extracts from Cultures of Certain Lactobacilli Inhibit Helicobacter pylori - Luc De Vuyst; Pascal Vincent; Eleftherios Makras; Frédéric Leroy; Bruno Pot (Probiotics and Antimicrobial Proteins, 2010)

Harmonin-b, an actin-binding scaffold protein, is involved in the adaptation of mechanoelectrical transduction by sensory hair cells - Nicolas Michalski; Vincent Michel; Elisa Caberlotto; Gaelle M. Lefèvre; Alexander F. J. van Aken; Jean-Yves Tinevez; Emilie Bizard; Christophe Houbron; Dominique Weil; Jean-Pierre Hardelin; Guy P. Richardson; Corné J. Kros; et al. (Pflügers Archiv - European Journal of Physiology, 2009)

Comparison of tree architecture using tree edit distances: application to 2-year-old apple hybrids - Vincent Segura; Aïda Ouangraoua; Pascal Ferraro; Evelyne Costes (Euphytica, 2008)

Regulation of the terpene moiety biosynthesis of Catharanthus roseus terpene indole alkaloids - Sabah Hedhili; Vincent Courdavault; Nathalie Giglioli-Guivarc’h; Pascal Gantet (Phytochemistry Reviews, 2007)

The dynamics of phosphorus in turbid estuarine systems: Example of the Gironde estuary (France) - Jonathan Deborde; Pierre Anschutz; Gwénaëlle Chaillou; Henri Etcheber; Marc-Vincent Commarieu; Pascal Lecroart; Gwenaël Abril (Limnology and Oceanography, 2007)
Suspended particles and surface waters were collected in the Gironde estuary (southwestern France) along the salinity gradient. Dissolved inorganic phosphorus (DIP) was analyzed in the filtered surface waters. The suspended particles were sequentially leached to determine five fractions of phosphorus: exchangeable or loosely sorbed P, reactive Fe‐bound P, refractory Fe oxide‐bound P, P associated with apatite and carbonates, and organic P. Experiments were conducted to determine the effects of temperature, salinity, and DIP concentration on phosphorus sorption/desorption processes. The concentration and distribution of particulate phosphorus was homogeneous along the salinity gradient of the estuary, whereas it was variable in time and space in the freshwater part. DIP showed a rapid desorption of loosely sorbed P at low salinities. Desorption depended on suspended particle concentration, but not on DIP concentration. At high suspended particle concentrations, some exchangeable P remained linked to particles, until suspended particle concentration decreased downstream of the estuary. This delayed desorption of bioavailable P occurs in waters in which the penetration of light is sufficient to support photosynthesis and probably plays a major role in primary production at high salinities. Mineralization of organic phosphorus also releases available phosphorus, but this process is slow relative to the water residence time in the estuary. The budget of DIP, the loss of particulate P from the organic fraction, and the water residence time suggest that the dynamics of P in the Gironde estuary is well explained by the two processes of P release from particles to waters without P uptake.

CaaX-prenyltransferases are essential for expression of genes involvedin the early stages of monoterpenoid biosynthetic pathwayin Catharanthus roseus cells - Vincent Courdavault; Martine Thiersault; Martine Courtois; Pascal Gantet; Audrey Oudin; Pierre Doireau; Benoit St-Pierre; Nathalie Giglioli-Guivarc’h (Plant Molecular Biology, 2005)

Mobility of metamorphic fluids inferred from infrared microspectroscopy on natural fluid inclusions: the example of Tinos Island, Greece - Vincent Famin; Satoru Nakashima; Laurent Jolivet; Pascal Philippot (Contributions to Mineralogy and Petrology, 2004)

Biological monitoring of workers exposed to low levels of 2-butoxyethanol - Vincent Haufroid; Françoise Thirion; Pascal Mertens; Jean-Pierre Buchet; Dominique Lison (International Archives of Occupational and Environmental Health, 1997)